PENGARUH KOMPETENSI, INDEPENDENSI, PROFESIONALISME, TINGKAT PENDIDIKAN, DAN PENGALAMAN TERHADAP KUALITAS AUDIT (Studi Empiris pada Kantor Akuntan Publik di Jawa Tengah dan Daerah Istimewa Yogjakarta) - GIMARDIEN, ZHELLA RACHMA (2017)
This study aims to examine and determine the effect of competence to audit quality. Test and determine the effect on the quality of audit independence. Testing and professionalism determine the effect on audit quality. Test and determine the effect of education on audit quality. Test and determine the effect of experience on audit quality. The population of this research is all auditors working on a Public Accounting Firm (KAP) in the Special Province of Yogyakarta and Central Java. The selection of the sample based on the ease (convenience sampling), this method of selecting a sample of the population elements (people or events) for which data are easily obtained by researchers. The total sample is the auditor. Wherein each of the public accounting firm of auditors are taken three partners, senior and junior auditors, because the researchers wanted to see the level of competence, independence, professionalism level of formal education and experience in influencing the quality audit of all three levels of the auditor. Based on the results of this study can be summarized as follows competence variables individually have influence on audit quality in Public Accounting Firm (KAP) in the Special Province of Yogyakarta and Central Java, the H1 is accepted. Variable independence individually have influence on audit quality in Public Accounting Firm (KAP) in the Special Province of Yogyakarta and Central Java, the H2 is accepted. Variable professionalism professionalism individually have influence on audit quality in Public Accounting Firm (KAP) in the Special Province of Yogyakarta and Central Java, the H3 is accepted. Variable levels of formal education has no effect on an individual basis on audit quality in Public Accounting Firm (KAP) in the Special Province of Yogyakarta and Central Java, the H4 is rejected. Variable experience individually has no effect on audit quality in Public Accounting Firm (KAP) in the Special Province of Yogyakarta and Central Java, the H5 is rejected.